Regulation of Energy Homeostasis by GPR41 - Inoue, Daisuke; Tsujimoto, Gozoh; Kimura, Ikuo (Frontiers in Endocrinology, 2014)
Imbalances in energy regulation lead to metabolic disorders such as obesity and diabetes. Diet plays an essential role in the maintenance of body energy homeostasis by acting not only as energy source but also as a signaling modality. Excess energy increases energy expenditure, leading to a consumption of them. In addition to glucose, mammals utilize short-chain fatty acids (SCFAs), which are produced by colonic bacterial fermentation of dietary fiber, as a metabolic fuel. The roles of SCFAs in energy regulation have remained unclear, although the roles of glucose are well studied. Recently, a G protein-coupled receptor (GPCR) deorphanizing strategy successfully identified GPR41 (also called free fatty acid receptor 3 or FFAR3) as a receptor for SCFAs. GPR41 is expressed in adipose tissue, gut, and the peripheral nervous system, and it is involved in SCFA-dependent energy regulation. In this mini-review, we focus on the role of GPR41 in host energy regulation.